Konsep Makanan Halal dan Haram dalam Perspektif Islam dan Kristen - Mahendra, Mhd. Rafiza; Andy, Safri; Faishal, M. (Lembaga Yasin AlSys, 2023)
Religion is a value system, and as such, it creates its own conflicts and challenges for experts and their adherents to arrive at values that are agreed upon by all parties. Humans need religion to fulfill their material needs, such as physical, biological and social needs, as well as their spiritual needs in order to function in society. As a result, God expects people to work hard to earn their gift sand food in a morally acceptable way. Humans always need food, which is one of their basic needs. Food processing must be good and right so that it is beneficial to the body. Anything made from biological sources or water, whether or not it has been processed, and intended to be consumed as food or drink, is considered food or food product. To limit human impulses as a means of self-defense, religion acts as a binder that also controls food.